MEMAHAMI ISLAM SECARA KAFFAH: INTEGRASI ILMU KEAGAMAAN DENGAN ILMU_ILMU UMUM - A. Rahman Ritonga (Islam Realitas: Journal of Islamic and Social Studies, 2016)
Islamic techings that called kaffah (absolute, universal and elastic) in accordance with the changes of times and the area in which he imposed. The absoluteness related to the user or object and material of teachings. In terms of material and dimensions, Islamic teachings derived from Qur'an and Hadith reach all human and genie problems whenever and wherever they are. The material that is charged to human not only aspects of sharia that consists of faith(akidah), worship(ibadah) and morality(akhlak) and Islamic laws, but reach all human needs in resolving problems and become their guidelines for life. This can be proved and felt when Islamic teachings was done in an integrative way through: a). Making use of Islam as the foundation of science (axiology) without questioning the ontological and epistimology aspect. b) insert values of Islam (tawhid) in a broad sense to the general sciences and technology. c) Integrating curriculum package of general sciences with religious knowledge in the educational process to born the experts of general sciences approach in understanding the religious science with science and technology. Ajaran Islam yang bersifat kaffah (absolut, universal dan elastis) sesuai dengan perubahan zaman dan wilayah dimana dia diberlakukan. Ke-kaffahannya terkait kepada pengguna atau objek dari ajarannya dan mataeri ajarannya. Dari segi materi dan dimensinya, ajaran Islam yang bersumber dari al-Qur’an dan hadis menjangkau semua persoalan manusia dan jin kapan dan dimanapun mereka berada. Materi yang dibebankan kepada manusia bukan saja aspek syariah yang terdiri dari akidah, ibadah dan akhlak sertah hukum-hukum Islam, melaikan menjankau semua kebutuhan manusia dalam menyesaikan persolan dan memnjadi pedoman mereka seumar hidup. Adapun pemahaman ajaran Islam itu dilakukan secara integratif melalui integrasi keilmuan berdasarkan al-Qur’an sunnah adalah: a). Menjadikan Islam sebagai landasan penggunaan ilmu (aksiologi) tanpa mempermasalahkan aspek ontologis dan epistimologisnya, b) memasukkan nilai-nilai Islam (tauhid) dalam arti luas ke dalam ilmu-ilmu umum dan teknologi, c) Mengintegrasikan paket kurikulum ilmu-ilmu umum dengan ilmu keagamaan dalam proses pendidikan untuk melahirkan ahli ilmu-ilmu umum, d) melakukan pendekatan dalam memahami ilmu keagamaan dengan sains dan teknologi.